2021
DOI: 10.1021/acs.jpca.1c03776
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Radiolysis Investigation of Radicals Derived from Water-Soluble Cyanine Dyes: Implications for Super-resolution Microscopy

Abstract: Light-induced blinking, an inherent feature of many forms of super-resolution microscopy, has been linked to transient reduction of the fluorescent cyanine dye used as an imaging agent. There is, however, only scant literature information related to one-electron reduced cyanine dyes, especially in an aqueous environment. Here, we examine a small series of cyanine dyes, possessing disparate π-conjugation lengths, under selective reducing or oxidizing conditions. The experiment allows recording of both different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…While a recent study identified the formation of a Cy5-thiol adduct with absorption maximum at 310 nm as off-state in dSTORM experiments 21 another study proposed the formation of a radical formed by one-electron reduction of the cyanine dye absorbing at roughly 450 nm (ref. 22 ). But, Cy5 fluorescence can be restored from the off-state also on irradiation with red light demonstrating that the off-state exhibits a very broad absorption spectrum 21 .…”
Section: Resultsmentioning
confidence: 99%
“…While a recent study identified the formation of a Cy5-thiol adduct with absorption maximum at 310 nm as off-state in dSTORM experiments 21 another study proposed the formation of a radical formed by one-electron reduction of the cyanine dye absorbing at roughly 450 nm (ref. 22 ). But, Cy5 fluorescence can be restored from the off-state also on irradiation with red light demonstrating that the off-state exhibits a very broad absorption spectrum 21 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 53 , 64 ] Likewise, deuterated polymethine cyanine dyes with a low propensity for photooxidative dimerization are promising future candidates for optimized super‐resolution microscopy. [65] …”
Section: Discussionmentioning
confidence: 99%
“…However, when the Cy5 •− feature is isolated from the one‐peak mix PIA features at 480 nm, the remaining signals closely match the signals of Cy5 •+ (Figure S10d, Supporting Information) reported in the literature through transient capturing. [ 20 ] Accordingly, one photon‐excited S 1 molecule can rapidly transfer charge to another nearby molecule in the ground state through SB‐CS in the molecular assembly, producing the Cy5 •− –Cy5 •+ CSS1. To further prove the SB‐CS charge transient mechanism, the TAS for Cy5 solid film was also measured (Figure S11a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%